Fluorescent dissolved oxygen sensing film, preparation method and fluorescent dissolved oxygen sensor
By using fluorescent dissolved oxygen sensing films prepared with polyimide and fluorine-containing raw materials, the problem of existing materials being not resistant to high temperatures is solved, and the high-temperature disinfection capacity and breathability are improved, which is suitable for a variety of application environments.
Patent Information
- Application Number
- CN202411940040.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
The existing fluorescent dissolved oxygen sensing film materials are not resistant to high temperatures and cannot undergo high temperature disinfection, which limits the application range of the sensor.
A high temperature-resistant fluorescent dissolved oxygen sensing film is prepared by using polyimide as the material of the sensing film, and a fluorine-containing dianhydride and/or fluorine-containing diamine as the synthetic raw material, and the viscosity of the polyamic acid is adjusted to improve breathability.
It realizes the high temperature disinfection ability of the sensor film, improves the sensor's response speed and detection accuracy, and meets the needs of the fluorescent dissolved oxygen sensor film in various application environments.
Smart Images

Figure BDA0005212387660000131 
Figure BDA0005212387660000141
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the field of sensor membrane technology, and specifically to a fluorescent dissolved oxygen sensor membrane, a preparation method, and a fluorescent dissolved oxygen sensor. Background Art
[0002] Fluorescent dissolved oxygen sensing membranes are mainly composed of fluorescent dyes, polymer matrices and auxiliary additives, and use the sensitivity of fluorescent substances to dissolved oxygen to achieve concentration detection. It is widely used in environmental monitoring, biomedicine and industrial production, such as water quality assessment, cell culture monitoring and fermentation process control, and has broad development prospects.
[0003] Currently, the polymer materials commonly used to make fluorescent dissolved oxygen sensor membranes are mainly cellulose acetate, polyethylene, polycarbonate, etc. These materials are not resistant to high temperatures and cannot be sterilized at high temperatures, which makes the sensor have certain limitations in application. Summary of the invention
[0004] In view of the above problems, the embodiments of the present application provide a fluorescent dissolved oxygen sensor membrane, a preparation method and a fluorescent dissolved oxygen sensor, which improve the high temperature resistance and air permeability of the sensor membrane.
[0005] According to one aspect of an embodiment of the present application, a method for preparing a fluorescent dissolved oxygen sensor membrane is provided, comprising:
[0006] Under a protective gas atmosphere, the diamine and dianhydride mixture is uniformly mixed with a polar solvent, and a polymerization reaction is carried out at 25-80° C. with stirring for 0.5-2 hours to obtain a polyamic acid solution, and the polar solvent is continuously added to adjust the viscosity of the polyamic acid solution to 40-100 cP, wherein the mass percentage of the diamine and dianhydride mixture is 5%-20%, the mass percentage of the polar solvent is 80%-95%, the molar ratio of the diamine to the dianhydride in the diamine and dianhydride mixture is 1:(0.8-1.5), and at least one of the diamine and the dianhydride contains fluorine;
[0007] Adding 0.01-5 wt % of the fluorescent indicator to the polyamic acid solution, and mixing evenly to obtain a mixed solution;
[0008] The mixed solution is applied to the surface of a substrate, and high-temperature cured under a protective gas atmosphere to form a fluorescent layer on the outer surface of the substrate;
[0009] The substrate with the fluorescent layer formed thereon is naturally cooled to room temperature to obtain a fluorescent dissolved oxygen sensor membrane.
[0010] In an optional manner, the diamine is one or more of 4,4'-diaminodiphenylmethane, 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenyl ether, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 2,2'-bis(trifluoromethyl)-4-diaminobiphenyl, and 2-(3,5-diaminophenyl)-benzimidazole.
[0011] In an optional manner, the dianhydride is one or more of 4,4′-(hexafluoroisopropylene) diphthalic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, 3,3'4,4'-benzophenonetetracarboxylic anhydride, pyromellitic anhydride, 4,4′-biphenyl ether dianhydride, phthalic anhydride, and cyclobutanetetracarboxylic anhydride.
[0012] In an optional manner, the mass percentage of the diamine and dianhydride mixture is 5%-12%, and the mass percentage of the polar solvent is 88%-95%.
[0013] In an optional manner, the mass percentage of the diamine and dianhydride mixture is 10%, and the mass percentage of the polar solvent is 90%.
[0014] In an optional manner, the molar ratio of diamine to dianhydride in the mixture of diamine and dianhydride is 1:(1-1.5).
[0015] In an optional manner, the molar ratio of diamine to dianhydride in the mixture of diamine and dianhydride is 1:1.
[0016] In an optional manner, the diamine is 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane, the dianhydride is 4,4′-(hexafluoroisopropylene)diphthalic anhydride, the mass percentage of the diamine and dianhydride mixture is 10%, the mass percentage of the polar solvent is 90%, the molar ratio of diamine to dianhydride in the diamine and dianhydride mixture is 1:1, and the viscosity of the polyamic acid solution is 70 cP.
[0017] According to another aspect of the embodiments of the present application, there is provided a fluorescent dissolved oxygen sensor membrane prepared by the method described in any one of the above embodiments.
[0018] According to another aspect of the embodiments of the present application, a fluorescent dissolved oxygen sensor is provided, wherein the fluorescent dissolved oxygen sensor comprises the fluorescent dissolved oxygen sensing membrane described above.
[0019] The present application prepares a fluorescent dissolved oxygen sensor membrane through polyimide, and in particular uses fluorinated dianhydride and / or fluorinated diamine as the synthetic raw materials of the sensor membrane, so that the prepared sensor membrane can resist high temperature disinfection, thereby meeting the application requirements of the fluorescent dissolved oxygen sensor membrane. In addition, the air permeability of the polyimide film is also improved, which can improve the response speed of the sensor using the fluorescent dissolved oxygen sensor membrane. Film formation is carried out when the viscosity of the polyamic acid is 40-100cP. The viscosity within this range is moderate, and the film thickness can be further controlled to improve the air permeability.
[0020] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0021] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0022] Fluorescent dissolved oxygen sensing membrane is a sensing membrane made by utilizing the property of fluorescent substances that are sensitive to changes in dissolved oxygen concentration. Its main components include fluorescent dyes, polymer matrices, and possible auxiliary additives. As the core of the sensing membrane, the fluorescent dye can interact with dissolved oxygen, causing changes in its fluorescence intensity or lifetime, thereby realizing the detection of dissolved oxygen concentration. The polymer matrix provides a stable support and dispersion environment to ensure the uniform distribution and long-term stability of the fluorescent dye. In addition, some auxiliary additives may be added as needed to optimize the performance of the sensing membrane, such as improving sensitivity, selectivity, and anti-interference ability.
[0023] Fluorescent dissolved oxygen sensor membranes have a wide range of applications in multiple fields. In the field of environmental monitoring, it can be used for real-time monitoring of dissolved oxygen in water bodies to help assess water quality and ecological health. In the biomedical field, fluorescent dissolved oxygen sensor membranes can be used in cell culture, tissue engineering and other occasions to monitor dissolved oxygen concentrations in microenvironments and provide important information for biological research and clinical applications. In addition, in industrial production processes such as fermentation and sewage treatment, fluorescent dissolved oxygen sensor membranes can also be used for process control and optimization to improve production efficiency and product quality. With the continuous advancement of technology and the in-depth expansion of applications, the future development prospects of fluorescent dissolved oxygen sensor membranes are very broad.
[0024] In the process of monitoring dissolved oxygen, the fluorescent dissolved oxygen sensor membrane may come into contact with various microorganisms, such as bacteria, algae, etc. These microorganisms will attach and grow on the membrane surface to form a biofilm, affecting the sensitivity and accuracy of the sensor membrane. The formation of biofilm will not only affect the measurement accuracy of the sensor, but may also cause aging or damage to the sensor membrane. High temperature disinfection can effectively kill these microorganisms, prevent biological contamination, and maintain the performance of the sensor and extend its service life. Therefore, the dissolved oxygen sensor membrane is required to be resistant to high temperature disinfection to ensure its long-term stable operation and improve measurement accuracy.
[0025] Currently, the polymer materials commonly used to make fluorescent dissolved oxygen sensor membranes are mainly cellulose acetate, polyethylene, polycarbonate, etc. These materials are not resistant to high temperatures and cannot be sterilized at high temperatures, which makes the sensor have certain limitations in application.
[0026] Based on this, the present application provides a method for preparing a fluorescent dissolved oxygen sensor membrane using polyimide. Polyimide is one of the organic polymer materials with the best comprehensive performance. It can withstand high temperatures of more than 400°C and has a long-term use temperature range of -200 to 300°C. The fluorescent dissolved oxygen sensor membrane prepared by polyimide can withstand high temperature disinfection, thereby meeting the application requirements of the fluorescent dissolved oxygen sensor membrane.
[0027] The preparation method of the fluorescent dissolved oxygen sensor membrane of the present application comprises the following steps:
[0028] S100, in a protective gas atmosphere, the diamine and dianhydride mixture is uniformly mixed with a polar solvent, and a polymerization reaction is carried out at 25-80° C. with stirring for 0.5-2 hours to obtain a polyamic acid solution, and the polar solvent is continuously added to adjust the viscosity of the polyamic acid solution to 40-100 cP.
[0029] The mass percentage of the mixture of diamine and dianhydride is 5%-20%, the mass percentage of the polar solvent is 80%-95%, and the molar ratio of diamine to dianhydride in the mixture of diamine and dianhydride is 1:(0.8-1.5).
[0030] The protective gas is nitrogen or argon. Carrying out the polymerization reaction under a nitrogen or argon atmosphere can prevent some sensitive steps in the polymerization process from being interfered with by oxygen. Specifically, diamines and dianhydrides may undergo oxidation reactions during the polymerization process, especially at high temperatures. Oxygen can react with diamines or dianhydrides, causing the structure and properties of the polymer to be affected. Nitrogen and argon are both inert gases and are not easy to react chemically with other substances, so they can provide an oxygen-free environment to prevent the occurrence of oxidation reactions. Carrying out the polymerization reaction under a nitrogen or argon atmosphere can also reduce impurities in the final product and improve the purity of the polymer. In the polymerization reaction, the presence of oxygen may affect the polymerization rate and degree of polymerization. By reacting under a nitrogen or argon atmosphere, the polymerization process can be more accurately controlled to obtain a polymer with the expected structure and properties. Nitrogen and argon can also help reduce the volatilization of solvents, especially at high temperatures. This helps to maintain the concentration of the reaction system and the stability of the reaction conditions. In general, carrying out the polymerization reaction under a protective gas atmosphere can prevent oxidation and other unnecessary side reactions. The protective gas can also be helium, carbon dioxide, hydrogen and other gases.
[0031] The diamine may be one or more of 4,4'-diaminodiphenylmethane, 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenyl ether, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 2,2'-bis(trifluoromethyl)-4-diaminobiphenyl, and 2-(3,5-diaminophenyl)-benzimidazole.
[0032] The dianhydride may be one or more of 4,4′-(hexafluoroisopropylene) diphthalic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, 3,3′4,4′-benzophenonetetracarboxylic anhydride, pyromellitic anhydride, 4,4′-biphenyl ether dianhydride, phthalic anhydride, and cyclobutanetetracarboxylic anhydride.
[0033] At least one of the diamine and the dianhydride contains fluorine.
[0034] Because the polar solvent contains polar bonds in its molecular structure, it can form effective interactions with reactant molecules such as diamine and dianhydride, thereby dissolving the above compounds well. The polar solvent can be one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, dimethyl sulfoxide, trifluoroacetic acid, acetonitrile, ethyl acetate, dichloromethane, and chloroform. The molecular structure of the above polar solvent contains oxygen atoms or other polar groups that can form hydrogen bonds, which helps to dissolve and stabilize the polyamic acid molecules, thereby promoting the polymerization reaction.
[0035] The 80%-95% polar solvent ratio helps ensure that the diamine and dianhydride are fully dissolved and promotes the polymerization reaction.
[0036] When adjusting viscosity, polar solvents can be added stepwise and the viscosity measured until the target viscosity in the range of 40-100 cP is reached.
[0037] S200, adding 0.01-5 wt % of a fluorescent indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0038] In this step, a fluorescent indicator is added to the polyamic acid solution obtained in step S100. The fluorescent indicator may be one or more of a metal porphyrin indicator, a metal pyridine indicator, and a metal o-phenanthroline indicator.
[0039] S300, coating the mixed solution on the surface of the substrate, and performing high-temperature curing under a protective gas atmosphere to form a fluorescent layer on the outer surface of the substrate.
[0040] The substrate can be polyethylene terephthalate (PET), polymethyl methacrylate (PMMA), polycarbonate (PC), polypropylene (PP) or glass. The thickness of the substrate is 0.1 to 5 mm.
[0041] The mixed solution can be applied to the surface of the substrate by spin coating, dip coating or scraping. Spin coating refers to dropping the mixed solution onto the rotating substrate, and the centrifugal force generated by the rotation makes the mixed solution spread evenly and form a thin film. Dip coating refers to immersing the substrate in the mixed solution and then slowly pulling it out to form a uniform coating. Scrape coating refers to using a scraper to evenly apply the mixed solution on the substrate, and the thickness of the film layer can be adjusted by controlling the moving speed and pressure of the scraper.
[0042] After coating, high temperature curing is required to ensure good adhesion and stability of the coating. The high temperature curing process is 0.5 to 1 hour at 100°C, 0.5 to 1 hour at 180°C, and 0.5 to 1 hour at 250 to 300°C. The protective gas can be nitrogen or argon. The thickness of the fluorescent layer is 10 to 50 μm.
[0043] S400, naturally cooling the substrate with the fluorescent layer formed thereon to room temperature to obtain a fluorescent dissolved oxygen sensing membrane.
[0044] Through this step, the substrate with the fluorescent layer formed thereon is subjected to low-temperature polycondensation to obtain a fluorescent dissolved oxygen sensor membrane.
[0045] The fluorescent dissolved oxygen sensing membrane prepared when using fluorine-containing dianhydride and / or fluorine-containing diamine as the synthetic raw materials of the sensing membrane is resistant to high temperature and can be sterilized at high temperature.
[0046] The air permeability of the polyimide film is also improved, and the response speed of the sensor using the fluorescent dissolved oxygen sensor film can be increased. The film is formed when the viscosity of the polyamic acid is 40-100 cP. The viscosity within this range is moderate, and the film thickness can be further controlled to improve the air permeability. Preferably, the film formation effect is best when the viscosity of the polyamic acid is 70 cP.
[0047] In some embodiments, after S400, the following steps may also be included:
[0048] S500, coating the reflective material solution on the surface of the substrate, drying at room temperature for 1 day, and forming a reflective layer on the outer surface of the substrate.
[0049] In this step, coating the reflective material solution on the substrate surface means coating the reflective material on the surface of the fluorescent layer of the substrate. The reflective material solution can be coated on the substrate surface by spin coating, dip coating or scraping.
[0050] The reflective layer is a polymer matrix and a white pigment dispersed in the matrix, the polymer matrix is one or more of epoxy resin, polyurethane, polyacrylate, carboxylic acid cellulose compound, and silicone rubber, and the white pigment is one or more of silicon dioxide, titanium dioxide, white carbon black, and talcum powder. The mass percentage of the white pigment is 0.5-10%, preferably 2-5%. Correspondingly, the mass percentage of the polymer matrix is 90-99.5%, preferably 95-98%. The thickness of the reflective layer is 20-60 μm.
[0051] By means of the above method, the outer layer of the fluorescent layer of the prepared fluorescent dissolved oxygen sensor membrane is provided with a reflective layer, which can enhance the fluorescent signal, improve the detection sensitivity, reduce background interference, increase the optical path length, and protect the fluorophore, thereby improving the performance of the sensor using the fluorescent dissolved oxygen sensor membrane, making it more sensitive, stable and reliable.
[0052] In some embodiments, after S500, the following steps may also be included:
[0053] S600, coating the light-shielding material solution on the surface of the substrate, and drying at room temperature for 1 day to form a light-shielding layer on the outer surface of the substrate.
[0054] In this step, coating the light-shielding material solution onto the substrate surface means coating the light-shielding material onto the surface of the reflective layer of the substrate. The light-shielding material solution can be coated onto the substrate surface by spin coating, dip coating or scraping.
[0055] The light-shielding layer is a polymer matrix and a black pigment dispersed in the matrix. The polymer matrix is one or more of styrene homopolymer, polyurethane, polyacrylate, carboxylic acid cellulose compound, silicone resin, polytetrafluoroethylene, polyvinylidene fluoride, and gypsum. The black pigment is preferably one or more of carbon black, pigment carbon black, iron black, and aniline black. There is no particular restriction on the content of the black pigment, which is generally 1 to 20% (mass percentage), and the mass percentage of the polymer matrix is 80-99% accordingly. The thickness of the light-shielding layer is 60 to 200 μm.
[0056] By means of the above method, the outermost layer of the prepared fluorescent dissolved oxygen sensor membrane is provided with a light shielding layer, which can prevent external light interference, improve the signal-to-noise ratio, and protect the sensor membrane.
[0057] In addition, the reflective layer and the light-shielding layer may also contain other components such as stabilizers, leveling agents, and plasticizers.
[0058] The embodiment of the present application also provides a fluorescent dissolved oxygen sensor membrane prepared by the above preparation method.
[0059] An embodiment of the present application also provides a dissolved oxygen sensor including the above-mentioned fluorescent dissolved oxygen sensing membrane.
[0060] The present application is further described in detail below with reference to specific embodiments.
[0061] Embodiment 1:
[0062] S100, under a nitrogen atmosphere, a mixture of 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane and 1,2,3,4-cyclobutanetetracarboxylic dianhydride was uniformly mixed with N,N-dimethylformamide, and the polymerization reaction was carried out at 60°C with stirring for 1 hour to obtain a polyamic acid solution, and N,N-dimethylformamide was continuously added to adjust the viscosity of the polyamic acid solution to 70 cP. The mass percentage of the mixture of 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane and 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride is 10%, the mass percentage of N,N-dimethylformamide is 90%, and the molar ratio of 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane to 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride in the mixture of 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane and 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride is 1:1.
[0063] S200, adding 1.5 wt % of a metal pyridine indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0064] S300, coating the mixed solution on a 2 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0065] S400, naturally cool to room temperature.
[0066] Embodiment 2:
[0067] S100, in a nitrogen atmosphere, a mixture of 4,4'-diaminodiphenylmethane and 4,4'-(hexafluoroisopropylene) diphthalic anhydride is uniformly mixed with N,N-dimethylformamide, and a polymerization reaction is carried out at 60°C with stirring for 1 hour to obtain a polyamic acid solution, and N,N-dimethylformamide is continuously added to adjust the viscosity of the polyamic acid solution to 70 cP. Among them, the mass percentage of the mixture of 4,4'-diaminodiphenylmethane and 4,4'-(hexafluoroisopropylene) diphthalic anhydride is 10%, the mass percentage of N,N-dimethylformamide is 90%, and the molar ratio of 4,4'-diaminodiphenylmethane and 4,4'-(hexafluoroisopropylene) diphthalic anhydride in the mixture of 4,4'-diaminodiphenylmethane and 4,4'-(hexafluoroisopropylene) diphthalic anhydride is 1:1.
[0068] S200, adding 1.5 wt % of a metal pyridine indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0069] S300, coating the mixed solution on a 2 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0070] S400, naturally cool to room temperature.
[0071] Embodiment 3:
[0072] S100, under a nitrogen atmosphere, a mixture of 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane and 4,4′-(hexafluoroisopropylene) diphthalic anhydride was uniformly mixed with N,N-dimethylformamide, and a polymerization reaction was carried out at 60°C with stirring for 1 hour to obtain a polyamic acid solution, and N,N-dimethylformamide was continuously added to adjust the viscosity of the polyamic acid solution to 70 cP. The mass percentage of the mixture of 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane and 4,4′-(hexafluoroisopropylene) diphthalic anhydride is 10%, the mass percentage of N,N-dimethylformamide is 90%, and the molar ratio of 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane and 4,4′-(hexafluoroisopropylene) diphthalic anhydride in the mixture of 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane and 4,4′-(hexafluoroisopropylene) diphthalic anhydride is 1:1.
[0073] S200, adding 1.5 wt % of a metal pyridine indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0074] S300, coating the mixed solution on a 2 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0075] S400, naturally cool to room temperature.
[0076] Embodiment 4:
[0077] S100, in a nitrogen atmosphere, a mixture of 2,2′-bis(trifluoromethyl)-4-diaminobiphenyl and 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride and tetrahydrofuran are uniformly mixed, and a polymerization reaction is carried out at 25°C with stirring for 2 hours to obtain a polyamic acid solution, and tetrahydrofuran is continuously added to adjust the viscosity of the polyamic acid solution to 100 cP. Among them, the mass percentage of the mixture of 2,2′-bis(trifluoromethyl)-4-diaminobiphenyl and 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride is 5%, the mass percentage of tetrahydrofuran is 95%, and the molar ratio of 2,2′-bis(trifluoromethyl)-4-diaminobiphenyl and 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride in the mixture is 1:1.5.
[0078] S200, adding 5 wt % of a metal o-phenanthroline indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0079] S300, coating the mixed solution on a 4 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0080] S400, naturally cool to room temperature. Embodiment 5:
[0081] S100, in a nitrogen atmosphere, the mixture of 2,2′-bis(trifluoromethyl)-4-diaminobiphenyl and pyromellitic anhydride was uniformly mixed with acetonitrile, and the polymerization reaction was carried out at 76°C with stirring for 0.5h to obtain a polyamic acid solution, and acetonitrile was continuously added to adjust the viscosity of the polyamic acid solution to 78cP. Among them, the mass percentage of the mixture of 2,2′-bis(trifluoromethyl)-4-diaminobiphenyl and pyromellitic anhydride was 12%, the mass percentage of acetonitrile was 88%, and the molar ratio of 2,2′-bis(trifluoromethyl)-4-diaminobiphenyl and pyromellitic anhydride in the mixture of 2,2′-bis(trifluoromethyl)-4-diaminobiphenyl and pyromellitic anhydride was 1:1.5.
[0082] S200, adding 0.8 wt % of a metal pyridine indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0083] S300, coating the mixed solution on a 1.6 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0084] S400, naturally cool to room temperature.
[0085] Comparative Example 1:
[0086] S100, in a nitrogen atmosphere, a mixture of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 3,3'4,4'-benzophenonetetracarboxylic dianhydride was uniformly mixed with trifluoroacetic acid, and a polymerization reaction was carried out at 45°C with stirring for 1.5 hours to obtain a polyamic acid solution, and trifluoroacetic acid was continuously added to adjust the viscosity of the polyamic acid solution to 86 cP. Among them, the mass percentage of the mixture of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 3,3'4,4'-benzophenonetetracarboxylic dianhydride was 16%, the mass percentage of trifluoroacetic acid was 84%, and the molar ratio of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 3,3'4,4'-benzophenonetetracarboxylic dianhydride in the mixture was 1:1.2.
[0087] S200, adding 3 wt % of a metal porphyrin indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0088] S300, coating the mixed solution on a 5 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 0.8 hour, 180° C. for 0.5 hour, and 250° C. for 0.6 hour.
[0089] S400, naturally cool to room temperature.
[0090] Comparative Example 2:
[0091] S100, in a nitrogen atmosphere, a mixture of 4,4'-diaminodiphenylmethane and 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride and N,N-dimethylformamide were uniformly mixed, and a polymerization reaction was carried out at 60°C with stirring for 1 hour to obtain a polyamic acid solution, and N,N-dimethylformamide was continuously added to adjust the viscosity of the polyamic acid solution to 70 cP. Among them, the mass percentage of the mixture of 4,4'-diaminodiphenylmethane and 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride was 10%, the mass percentage of N,N-dimethylformamide was 90%, and the molar ratio of 4,4'-diaminodiphenylmethane and 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride in the mixture was 1:1.
[0092] S200, adding 1.5 wt % of a metal pyridine indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0093] S300, coating the mixed solution on a 2 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0094] S400, naturally cool to room temperature.
[0095] Comparative Example 3:
[0096] S100, in a nitrogen atmosphere, the mixture of 4,4'-diaminodiphenylmethane and phthalic anhydride is uniformly mixed with N-methylpyrrolidone, and the polymerization reaction is carried out at 80°C with stirring for 0.5h to obtain a polyamic acid solution, and N-methylpyrrolidone is continuously added to adjust the viscosity of the polyamic acid solution to 52cP. Among them, the mass percentage of the mixture of 4,4'-diaminodiphenylmethane and phthalic anhydride is 8%, the mass percentage of N-methylpyrrolidone is 92%, and the molar ratio of 4,4'-diaminodiphenylmethane and phthalic anhydride in the mixture of 4,4'-diaminodiphenylmethane and phthalic anhydride is 1:0.9.
[0097] S200, adding 2 wt % of a metal o-phenanthroline indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0098] S300, coating the mixed solution on a 1 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0099] S400, naturally cool to room temperature.
[0100] Comparative Example 4:
[0101] S100, in a nitrogen atmosphere, a mixture of 2-(3,5-diaminophenyl)-benzimidazole and cyclobutane tetracarboxylic acid dianhydride and N,N-dimethylacetamide were uniformly mixed, and a polymerization reaction was carried out at 32°C with stirring for 1.5 hours to obtain a polyamic acid solution, and N,N-dimethylacetamide was continuously added to adjust the viscosity of the polyamic acid solution to 40 cP. Among them, the mass percentage of the mixture of 2-(3,5-diaminophenyl)-benzimidazole and cyclobutane tetracarboxylic acid dianhydride was 14%, the mass percentage of N,N-dimethylacetamide was 86%, and the molar ratio of 2-(3,5-diaminophenyl)-benzimidazole and cyclobutane tetracarboxylic acid dianhydride in the mixture was 1:0.8.
[0102] S200, adding 0.01 wt % of a metal o-phenanthroline indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0103] S300, coating the mixed solution on a 0.1 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0104] S400, naturally cool to room temperature.
[0105] Comparative Example 5:
[0106] S100, in a nitrogen atmosphere, a mixture of 2-bis[4-(4-aminophenoxy)phenyl]propane and 4,4′-biphenyl ether dianhydride was uniformly mixed with dimethyl sulfoxide, and a polymerization reaction was carried out at 50°C with stirring for 1.5 hours to obtain a polyamic acid solution, and dimethyl sulfoxide was continuously added to adjust the viscosity of the polyamic acid solution to 65 cP. Among them, the mass percentage of the mixture of 2-bis[4-(4-aminophenoxy)phenyl]propane and 4,4′-biphenyl ether dianhydride was 20%, the mass percentage of dimethyl sulfoxide was 80%, and the molar ratio of 2-bis[4-(4-aminophenoxy)phenyl]propane and 4,4′-biphenyl ether dianhydride in the mixture of 2-bis[4-(4-aminophenoxy)phenyl]propane and 4,4′-biphenyl ether dianhydride was 1:1.1.
[0107] S200, adding 4.5 wt % of a metal pyridine indicator to the polyamic acid solution, and mixing the mixture evenly to obtain a mixed solution.
[0108] S300, coating the mixed solution on a 3.5 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0109] S400, naturally cool to room temperature.
[0110] Comparative Example 6:
[0111] S100, in a nitrogen atmosphere, cellulose acetate and N,N-dimethylformamide were mixed evenly, and the polymerization reaction was carried out at 60°C with stirring for 1 hour, and N,N-dimethylformamide was continuously added to adjust the viscosity of the solution to 70 cP. The mass percentage of cellulose acetate was 10%, and the mass percentage of N,N-dimethylformamide was 90%.
[0112] S200, adding 1.5 wt % of a metal pyridine indicator to the solution, mixing the mixture evenly, and obtaining a mixed solution.
[0113] S300, coating the mixed solution on a 2 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0114] S400, naturally cool to room temperature.
[0115] Comparative Example 7:
[0116] S100, in a nitrogen atmosphere, polycarbonate and N,N-dimethylformamide were uniformly mixed, and the polymerization reaction was carried out at 60° C. with stirring for 1 hour, and N,N-dimethylformamide was continuously added to adjust the viscosity of the solution to 70 cP, wherein the mass percentage of polycarbonate was 10% and the mass percentage of N,N-dimethylformamide was 90%.
[0117] S200, adding 1.5 wt % of a metal pyridine indicator to the solution, mixing the mixture evenly, and obtaining a mixed solution.
[0118] S300, coating the mixed solution on a 2 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0119] S400, naturally cool to room temperature.
[0120] Comparative Example 8:
[0121] S100, in a nitrogen atmosphere, polyethylene and N,N-dimethylformamide were mixed evenly, and the polymerization reaction was carried out at 60°C with stirring for 1 hour, and N,N-dimethylformamide was continuously added to adjust the viscosity of the solution to 70 cP. The mass percentage of polyethylene was 10%, and the mass percentage of N,N-dimethylformamide was 90%.
[0122] S200, adding 1.5 wt % of a metal pyridine indicator to the solution, mixing the mixture evenly, and obtaining a mixed solution.
[0123] S300, coating the mixed solution on a 2 mm thick glass surface, and performing high temperature curing in a nitrogen atmosphere, reacting at 100° C. for 1 hour, 180° C. for 1 hour, and 250° C. for 1 hour.
[0124] S400, naturally cool to room temperature.
[0125] The high temperature resistance and air permeability of the above embodiments and comparative examples were tested. First, a high temperature resistance test was performed. The high temperature resistance test was performed by heating in a vacuum drying oven. After the temperature was raised to 280°C, the temperature was restored to room temperature to observe whether the properties of the sensor membrane changed and whether the fluorescence effect of the test sensor membrane still met the application conditions. The products that passed the high temperature resistance test were then subjected to an air permeability test. The air permeability test was performed by testing the response time of the sensor membrane from a saturated oxygen partial pressure environment to an oxygen-free environment. The shorter the time, the better the air permeability. The above uses the Frog Vision 610114 dissolved oxygen meter to detect the fluorescence and sensing characteristics of the sensor membrane.
[0126] The test results are shown in Table 1:
[0127] Table 1
[0128]
[0129]
[0130] It can be seen that the fluorescent dissolved oxygen sensor membrane made of fluorinated dianhydride and / or fluorinated diamine as the synthetic raw material of the sensor membrane has significantly improved high temperature resistance compared with the fluorescent dissolved oxygen sensor membrane made of cellulose acetate, polyethylene, polycarbonate and other materials and fluorine-free dianhydride and / or diamine. When the viscosity of the polyamic acid solution is 70cP, the air permeability of the prepared sensor membrane is the best.
[0131] In Example 3, in which the diamine is 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane, the dianhydride is 4,4′-(hexafluoroisopropylene)diphthalic anhydride, the mass percentage of the diamine and dianhydride mixture is 10%, the mass percentage of the polar solvent is 90%, the molar ratio of diamine to dianhydride in the diamine and dianhydride mixture is 1:1, and the viscosity of the polyamic acid solution is 70 cP, the product passes the high temperature resistance test and has the best air permeability.
[0132] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in the embodiments of the present application should have the common meanings understood by technicians in the field to which the embodiments of the present application belong.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application is described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A method for preparing a fluorescent dissolved oxygen sensor membrane, characterized in that: include: Under a protective gas atmosphere, the diamine and dianhydride mixture is uniformly mixed with a polar solvent, and a polymerization reaction is carried out at 25-80° C. with stirring for 0.5-2 hours to obtain a polyamic acid solution, and the polar solvent is continuously added to adjust the viscosity of the polyamic acid solution to 40-100 cP, wherein the mass percentage of the diamine and dianhydride mixture is 5%-20%, the mass percentage of the polar solvent is 80%-95%, the molar ratio of the diamine to the dianhydride in the diamine and dianhydride mixture is 1:(0.8-1.5), and at least one of the diamine and the dianhydride contains fluorine; Adding 0.01-5 wt % of the fluorescent indicator to the polyamic acid solution, and mixing evenly to obtain a mixed solution; The mixed solution is applied to the surface of a substrate, and high-temperature cured under a protective gas atmosphere to form a fluorescent layer on the outer surface of the substrate; The substrate with the fluorescent layer formed thereon is naturally cooled to room temperature to obtain a fluorescent dissolved oxygen sensor membrane.
2. The method according to claim 1, characterized in that The diamine is one or more of 4,4'-diaminodiphenylmethane, 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenyl ether, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 2,2'-bis(trifluoromethyl)-4-diaminobiphenyl, and 2-(3,5-diaminophenyl)-benzimidazole.
3. The method according to claim 1, characterized in that The dianhydride is one or more of 4,4′-(hexafluoroisopropylene) diphthalic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, 3,3′4,4′-benzophenonetetracarboxylic anhydride, pyromellitic anhydride, 4,4′-biphenyl ether dianhydride, phthalic anhydride, and cyclobutanetetracarboxylic anhydride.
4. The method according to claim 1, characterized in that: The mass percentage of the diamine and dianhydride mixture is 5%-12%, and the mass percentage of the polar solvent is 88%-95%.
5. The method according to claim 1, characterized in that The mass percentage of the diamine and dianhydride mixture is 10%, and the mass percentage of the polar solvent is 90%.
6. The method according to claim 1, characterized in that The molar ratio of diamine to dianhydride in the diamine and dianhydride mixture is 1:(1-1.5).
7. The method according to claim 1, characterized in that The molar ratio of diamine to dianhydride in the diamine and dianhydride mixture is 1:
1.
8. The method according to claim 1, characterized in that The diamine is 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane, the dianhydride is 4,4′-(hexafluoroisopropylene)diphthalic anhydride, the mass percentage of the diamine and dianhydride mixture is 10%, the mass percentage of the polar solvent is 90%, the molar ratio of diamine to dianhydride in the diamine and dianhydride mixture is 1:1, and the viscosity of the polyamic acid solution is 70 cP.
9. A fluorescent dissolved oxygen sensor membrane prepared by the method according to any one of claims 1 to 8.
10. A fluorescent dissolved oxygen sensor, characterized in that: The fluorescent dissolved oxygen sensor comprises the fluorescent dissolved oxygen sensing membrane according to claim 9.